Elastic constants and optical phonon frequencies of BX (X= P, As, and Sb) semiconductors: Semi-empirical prediction - Daoud, Salah; Kumar Saini, Pawan; Rekab-Djabri, Hamza (International Journal of Physical Research, 2020)
Based on some simple empirical formulas established by Adachi in, Properties of group-IV, III-V and II-VI semiconductors, John Wiley & Sons, Chichester (2005), and the experimental lattice constants reported in the literature; the present work aims to predict the elastic constants and some other significant properties of cubic zinc-blende boron compounds (BP, BAs and BSb). The obtained values of C12and C44 are in general good agreement with other data of the literature, while C11 and B are slightly lower. The zone-center longitudinal optical (LO) and transverse optical (TO) phonon frequencies are also obtained. The LO and TO phonon frequencies of BP compound were found at 866.6and 834.5 cmâ€“1, respectively; these of BAs were found at 731.3 and 727.1 cmâ€“1, respectively; while for the BSb narrow-gap semiconducting compound were found at around 598.3and 586.2 cmâ€“1, respectively. These two later values are in general slightly lower than the calculated values, and the observed Raman spectroscopy values reported in the literature.Â